PWE-109 A Metabolomic Profiling Study Of A Chemically-induced Mouse Model Of Intestinal Inflammation. (9th June 2014) - Reade, S; Duckworth, CA; Khalid, T; Mayor, A; Aggio, R; Pritchard, DM; Probert, CS
Abstract : Introduction: A non-invasive, IBD-specific biomarker would be clinically useful. We have reported the changes in volatile organic metabolites (VOM) in human IBD. Human studies are limited by the variation in diet and the unpredictability of the disease. Animal models have been established to study many aspects of IBD. We report the first study of VOMs in murine DSS-colitis. Methods: C57BL/6 female mice at 9–10 weeks old were administered 4.25% dextran sulphate sodium (DSS) in their drinking water for 5 days in order to induce colitis. Clinical parameters of body weight loss, stool consistency and presence of rectal bleeding were assessed daily. Mice were culled at days 0 (n = 11), 5 (n = 11), 8 (n = 11) and 11 (n = 8); colonic, caecal, small bowel contents, mid-large bowel and distal small bowel tissue were taken. VOM profiles for each were analysed using SPME with a CAR/PDMS/DVB fibre and gas chromatography-mass spectrometry. Histology of the distal colon confirmed the presence of colitis; this was graded from none to mild or moderate/severe. Results: Histology confirmed the presence of colitis. VOM profiles for each sample at days 5, 8 and 11 were compared with day 0. The presence/absence data were used as independent variables in a chi-squared statistical test. In the colonic content, 106 compounds were identified across all groups; 13, 22 and 10 significantly varied with presence/absence between day 0 and day 5, 8 and 11, respectively. A t-test was performed on the abundance of compounds present in at least 60% of samples in one condition. A total of 29 compounds were identified; 9, 6 and 7 VOCs were present at significantly different levels between day 0 and day 5, 8 and 11, respectively. Significance levels for both chi-squared and t-tests were set at p < 0.05 and a fold difference of ³2. Principal component analysis (PCA) of the raw data showed clear separation between the different stages of the disease. A PCA biplot revealed that butanal, propanal, methyl propionate, ethyl acetate, ethyl propionate and 2, 3-butanedione were responsible for the main separation between day 0 and day 5/8 of colitis. Conclusion: Typical clinical and histological features of colitis commenced on day 5, were maximal at day 8 and mice showed signs of recovery between days 8 and 11. The VOM results reflect this timescale, suggesting that metabolic disease profiling is able to represent the different stages of colitis. Further investigation of these differences could deepen our understanding of the pathogenesis of IBD. Disclosure of Interest: None Declared.